Laser-induced tuning of graphene field-effect transistors for pH sensing. Issue 15 (3rd April 2023) - Lampinen, Aku; See, Erich; Emelianov, Aleksei; Myllyperkiö, Pasi; Johansson, Andreas; Pettersson, Mika
Abstract : A demonstration of a proof-of-concept application of a novel photo-chemical oxidation method of graphene. This fast, easy, and highly controllable method improves pH sensitivity via local functionalization. Abstract : Here we demonstrate, using pulsed femtosecond laser-induced two-photon oxidation (2PO), a novel method of locally tuning the sensitivity of solution gated graphene field-effect transistors (GFETs) without sacrificing the integrity of the carbon network of chemical vapor deposition (CVD) grown graphene. The achieved sensitivity with 2PO was (25 ± 2) mV pH −1 in BIS-TRIS propane HCl (BTPH) buffer solution, when the oxidation level corresponded to the Raman peak intensity ratio I (D)/ I (G) of 3.58. Sensitivity of non-oxidized, residual PMMA contaminated GFETs was 20–22 mV pH −1 . The sensitivity decreased initially by 2PO to (19 ± 2) mV pH −1 ( I (D)/ I (G) = 0.64), presumably due to PMMA residue removal by laser irradiation. 2PO results in local control of functionalization of the CVD-grown graphene with oxygen-containing chemical groups enhancing the performance of the GFET devices. The GFET devices were made HDMI compatible to enable easy coupling with external devices for enhancing their applicability.